Diversity and antibiotic resistance of cultivable bacteria in bulk tank milk from dairy farms in Shandong Province, China - Qi, Yijian; Lu, Zhiyuan; Meng, Ziru; Wang, Xiaozhou; Chen, Huahua; Li, Muzi; Qu, Chaonan; Zhang, Pu; Liu, Yongxia; Liu, Jianzhu (Frontiers in Veterinary Science, 2025)
IntroductionThis study systematically analyzed bacterial diversity and antimicrobial resistance (AMR) profiles in bulk tank milk from five dairy farms (n = 30) in Shandong Province, China, to assess public health risks associated with microbial contamination and provide critical data for regional quality control and AMR risk assessment in dairy production systems.MethodsTotal bacterial counts were quantified, revealing significant inter-farm variation (P < 0.05) with a range of 3.94–6.68 log CFU/mL. Among 129 bacterial isolates, genus-level dominance and species prevalence were identified. Antimicrobial susceptibility testing (AST) against 10 agents was performed using integrated resistance criteria combining Clinical and Laboratory Standards Institute (CLSI) standards and epidemiological cutoff values (ECOFFs). Nine resistance genes targeting seven antibiotic classes were detected via PCR.ResultsThe highest resistance rate was observed for sulfadiazine (53.2%) and the lowest for levofloxacin (6.0%). Multidrug resistance was detected in 23% (20/87) of isolates, with 14 strains meeting ECOFFs-based resistance criteria. PCR analysis showed sul1 (70.5%) and ant(4′)-Ia (54.3%) as the most prevalent resistance genes, while mcr-1, lnu (B), and blaNDM-1 were absent in all isolates. Regional resistance variations correlated significantly with farm management practices.DiscussionThese findings underscore the impact of historical antibiotic use on AMR dissemination. Enhanced AMR surveillance in raw milk, improved antibiotic stewardship, and targeted interventions are crucial to mitigate public health risks from microbial contamination and horizontal gene transfer of resistance determinants.